4xy-x(y-3)=

Simple and best practice solution for 4xy-x(y-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4xy-x(y-3)= equation:


Simplifying
4xy + -1x(y + -3) = 0

Reorder the terms:
4xy + -1x(-3 + y) = 0
4xy + (-3 * -1x + y * -1x) = 0
4xy + (3x + -1xy) = 0

Reorder the terms:
3x + 4xy + -1xy = 0

Combine like terms: 4xy + -1xy = 3xy
3x + 3xy = 0

Solving
3x + 3xy = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '3x'.
3x(1 + y) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(1 + y)' equal to zero and attempt to solve: Simplifying 1 + y = 0 Solving 1 + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + y = 0 + -1 y = 0 + -1 Combine like terms: 0 + -1 = -1 y = -1 Add '-1y' to each side of the equation. y + -1y = -1 + -1y Combine like terms: y + -1y = 0 0 = -1 + -1y Simplifying 0 = -1 + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

x = {0}

See similar equations:

| -8n+4(1+5n)=-6n+14 | | (a+4)2=a | | -6.7=1y-27 | | 17-2x=17-2x | | -3+5=-3(9x+1) | | 1b+-9=36 | | 5x^3-16x^2-21x=0 | | 7.5/4.3=X/3.75 | | (-8)-3(-5)= | | 40+15+0.25(100)=45+0.35(100) | | 2/5y=1/5x+8/5 | | x^3+2x=144 | | 7.50x+y=395 | | -7-4(1+9d)=20 | | 1/3+x=1/2 | | 40+15+0.25(10)=45+0.35(10) | | 2a+6=-3a+2 | | 7(t+4)-3(l+t)=19 | | x^2-4=2x(x-2) | | y-13=-20 | | 2a+6=3a-2 | | 16+-9=36 | | x^3+2x^2=144 | | -7h+4=-2h-16 | | 9-(-11a)-7=-1 | | x(x+28)=196 | | (2x-5)(7x+1)(3x-7)=0 | | 1t+12=-18 | | h-4/5=56/5 | | -y+18=-3 | | 8+10r-2=9r+12-2r | | -7y+4x=18 |

Equations solver categories